Erratic fruit set in almond under warm climates - Kodad, O.; Socias I Company, R. (International Journal of Horticultural Science, 2014)
The cause for the erratic yields of the two main almond cultivars grown in Morocco has been searched in order to recommend possible solutions for a high and stable production. The lack of sufficient bloom overlap between ‘Marcona’ and ‘Fournat de Brézenaud’ in many years may be one of the reasons of this erratic behavior, but not the only one, as the same behaviour may be observed in two simultaneously blooming cultivars, ‘Ferragnès’ and ‘Ferraduel’. The relatively high temperatures observed during the blooming period significantly reduced the stigma receptivity of these cultivars and, as a consequence, their effective pollination period, showing that stigmatic receptivity is a limiting factor for fruit set in ‘Marcona’ and ‘Ferragnès’ and their subsequent yield reduction under warm conditions. Thus, in the present context of global warming, the search for cultivars tolerant to heat stress during flowering will acquire a special interest, as well as the combination of cultivars with the same chilling and heat requirements to ensure a simultaneous bloom.